Prevalence of thrombocytopenia in chronic hepatitis c patients arriving in out patient department - Haris Raza; Abdul Shakoor Shakir; Awais Amin; Rizwan Zafar (Medical Journal of South Punjab, 2025)
Objective: To determine the prevalence of thrombocytopenia in chronic Hepatitis-C patients presenting at the outdoor patients department of Farooq Hospital, Lahore. Methodology: A Cross-sectional study was conducted in the medical outdoor patients department of Farooq Hospital, Lahore, from September 1st, 2023, to August 31st, 2024. Four hundred patients with hepatitis who were either newly diagnosed or taking treatment for the last 3 months and those who had relapse/failure to treatment were enrolled. After recording the baseline, their blood samples for serum platelet counts were withdrawn. Thrombocytopenia was labeled based on platelet counts of ?150,000 uL. The prevalence of thrombocytopenia was presented as frequency and percentage. Results: The mean age of patients was 41.18±6.51 years. There were 271 (67.7%) males. Diabetes, hypertension, and I.H.D. were found in 54 (13.5%), 69 (17.3%), and 29 (7.3%) patients. The mean duration since hepatitis C of the patients was 6.63±1.99 months. The mean platelet count of the patients was 160.77±62.46 ×(103/uL), and there were 151 (37.8%) patients had ?150 platelet count. Thrombocytopenia was severe in 16 (10.6%) patients, moderate in 92 (60.9%) patients and mild in 43 (28.5%) patients. Since Hepatitis C was diagnosed, the mean duration was greater in severe thrombocytopenia than in mild and moderate thrombocytopenia (p<0.001). Conclusion: Thrombocytopenia is a marker of severity in patients with hepatitis C, depicting its extrahepatic manifestation. The percentage of severe thrombocytopenia was higher in patients with longer durations, with features of cirrhosis.